Problematic areas in the real property subjects to a fiduciary domain: sales tax treatment and the provisionary measures - Pozo Sánchez, Julio (2017)
According to Peruvian legislation, through an escrow agreement a trustor transfers under a fiduciary domain in favor of an escrow agent various goods, rights and obligations, which must achieve certain purpose. These will constitute an autonomous patrimony that does not respond any obligation of the trustor and the agent escrow. Despite the clarity of this statement, the authors reveal that indeed there might be different interpretations about this agreement that have practical consequences with the treatment of real properties subject to fiduciary dominion.